Fatigue Life Assessment of SAE 1045 Carbon Steel under Strain Events using the Weibull Distribution / Mazian Mohammad...[et al.] - Mohammad, Mazian; Abdullah, Shahrum; Jamaludin, Nordin; Innayatullah, Othman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The Weibull distribution has been widely used in predicting fatigue life of various materials. In this paper, the Weibull distribution plot is proposed in predicting fatigue life of carbon steel. The specimens made of SAE 1045 steel have been exposed to the cyclic test with five different loadings. The strain gauge has been attached on the specimen to collect the strain events. The cyclic tests were carried out at condition of R=-1 and at frequency of 8 Hz. The collected signals were then analysed based on the strain life model of Coffin-Manson, Smith-Watson-Topper and Morrow. These models provide the basis in predicting the fatigue life of SAE 1045 carbon steel. Statistical analysis was carried out to determine the strain range, root means square (r.m.s) and kurtosis value. From the Weibull distribution probability plots, fatigue lives was predicted for SAE 1045 carbon steel based on the given parameters. All plots fitted very well within the 95% confidence interval of the Weibull distribution. Hence, Weibull distribution was suggested to be used as one of assessment tool for fatigue life prediction.